Patient-reported outcome measures for knowledge transfer and behaviour modification interventions in type 2 diabetes—the INDICA study: a multiarm cluster randomised controlled trial - Amado Rivero-Santana; Leopoldo Martin Martin; Marta Riaño Ruiz; Yolanda Ramallo-Fariña; Montserrat Carmona; Mauro Boronat; Leticia Rodríguez-Rodríguez; Lidia García-Pérez; Miguel Angel García-Bello; Ana Maria Wägner; Himar Gonzalez-Pacheco; Sybille Kaiser-Girardot; et al. (BMJ Open)
Objective This study assesses the effectiveness of different interventions of knowledge transfer and behaviour modification to improve type 2 diabetes mellitus patients’ (T2DM) reported outcomes measures (PROMs) in the long-term. Design: open, community-based pragmatic, multicentre, controlled trial with random allocation by clusters to usual care (UC) or to one of the three interventions.Participants A total of 2334 patients with uncomplicated T2DM and 211 healthcare professionals were included of 32 primary care centres.Setting Primary Care Centers in Canary Islands (Spain).Intervention The intervention for patients (PTI) included an educational group programme, logs and a web-based platform for monitoring and automated short message service (SMS). The intervention for professionals (PFI) included an educational programme, a decision support tool embedded into the electronic clinical record and periodic feedback about patients’ results. A third group received both PTI and PFI (combined intervention, CBI).Outcome measure Cognitive-attitudinal, behavioural, affective and health-related quality of life (HQoL) variables.Results Compared with UC at 24 months, the PTI group significantly improved knowledge (p=0.005), self-empowerment (p=0.002), adherence to dietary recommendations (p<0.001) and distress (p=0.01). The PFI group improved at 24 months in distress (p=0.03) and at 12 months there were improvements in depression (p=0.003), anxiety (p=0.05), HQoL (p=0.005) and self-empowerment (p<0.001). The CBI group improved at 24 months in self-empowerment (p=0.008) and adherence to dietary recommendations (p=0.004) and at 12 months in knowledge (p=0.008), depression (p=0.006), anxiety (p=0.003), distress (p=0.01), HQoL (p<0.001) and neuropathic symptoms (p=0.02). Statistically significant improvements were also observed at 24 months in the proportion of patients who quit smoking for PTI and CBI (41.5% in PTI and 42.3% in CBI vs 21.2% in the UC group).Conclusions Assessed interventions to improve PROMs in T2DM attain effectiveness for knowledge, self-empowerment, distress, diet adherence and tobacco cessation. PTI produced the most lasting benefits.Trial registration number ClinicalTrials.gov NCT01657227 (6 August 2012) https://clinicaltrials.gov/ct2/show/NCT01657227.